Academic writing in university education - Coronado López, Sandra Paola (2021)
Academic writing is a social practice, an activity that communicates the knowledge generated in different disciplines that use scientific research and reflection as a central task. Academic writing is a dimension of epistemic task and is part of the work of production and teaching of knowledge in university community spaces. In this context, academic writing takes shape in the academic discursive genre and includes a variety of textual classes with different cognitive-communicative functions: monographs, essays, research projects, research reports, research articles, academic articles, academic reviews, papers, theses. This article systematically reviews a body of research conducted on the undergraduate teaching of academic writing. The objective is to identify tendencies of scientific knowledge about this literate practice in university teaching spaces. A corpus of 20 scientific articles published in the period 2017-2021 was analyzed. The information was processed and systematized analytically-descriptively. The results show that the articles report research conducted in Latin American (Mexico, Colombia, Chile, Argentina, Peru) and European (Spain) universities, in areas of Humanities (Psychology, History, Philosophy, Education) and Sciences (Mechanical Engineering and Biochemistry). In conclusion, this work synthesized the relevant information in relation to academic writing, which is assumed to have an epistemic function, since it allows the construction of knowledge, an activity that occurs during higher education and who is essential for a better development of this skill. Keywords: writing, academic writing, academic writing, university writing.